2018
DOI: 10.15406/mojph.2018.07.00224
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-lipoic acid: mechanisms of action and beneficial effects in the prevention and treatment of diabetic complications

Abstract: Alpha-lipoic acid (ALA) has been widely prescribed drug for treatment and prevention of diabetic complications since it affects the main pathogenesis links. ALA has many biochemical functions acting as a biological antioxidant, anti-inflammatory properties, metal chelators, reducing the oxidized forms of other antioxidant agents such as vitamin C and E and glutathione, and modulating the signaling transduction of several pathways, like insulin and nuclear factor kappa-light-chain-enhancer of activated B cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Testicular sections of rats received ALA had normal seminiferous tubules with complete spermatogenesis and normal interstitial connective tissue figures (13, 14,) in comparison to control figure (15,16). H2O2 treated rats group T2 exhibited histopathological alterations in thewith degenerative changes of majority of seminiferous tubules characterized with incomplete spermatogenesis and edema figure (17 ). Besides the majority of seminiferous tubules were almost devoid of spermatids and spermatozoa with vacuolar degeneration of spermatogonia , Sertoli cells and Leydigs cells which evoked on cessation of spermatogenesis figures (18,19) .…”
Section: Vol 13mentioning
confidence: 97%
See 1 more Smart Citation
“…Testicular sections of rats received ALA had normal seminiferous tubules with complete spermatogenesis and normal interstitial connective tissue figures (13, 14,) in comparison to control figure (15,16). H2O2 treated rats group T2 exhibited histopathological alterations in thewith degenerative changes of majority of seminiferous tubules characterized with incomplete spermatogenesis and edema figure (17 ). Besides the majority of seminiferous tubules were almost devoid of spermatids and spermatozoa with vacuolar degeneration of spermatogonia , Sertoli cells and Leydigs cells which evoked on cessation of spermatogenesis figures (18,19) .…”
Section: Vol 13mentioning
confidence: 97%
“…It has been reported that ALA have powerful antioxidant abilities, equal to that of coenzyme Q 10, vitamin C, and vitamin E (16). Unlike other antioxidants, ALA alpha lipoic acid has ability to neutralize free radicals in intracellular and extracellular environments (17).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms involved in the protective effects against lead and zinc oxide nanoparticles can be postulated depending on the previous studies. ALA improves the redox state of the plasma and shows a protective effect on oxidative stress-induced apoptosis (Serhiyenko et al, 2018). One study of α-LA against hydrogen peroxide-induced toxicity in human lymphocytes showed it to be an ideal compound that has profound protective effects on oxidation, inflammation, and apoptosis (Rahimifard et al, 2015).…”
Section: Leónmentioning
confidence: 99%
“…Stimulating adenosine monophosphate-activated protein kinase, with each of these components having numerous consequences. 21,26,36,37 The positive influences of ALA on such metabolic and functional parameters are partly confirmed by its neurotropic, cardioprotective, angioprotective and cytoprotective properties; this finding suggests its usefulness in the treatment of T2D patients with diabetic cardiac autonomic neuropathy.…”
Section: Discussionmentioning
confidence: 92%